Harmonizing Confucianism in Nepali Higher Education System: A Thematic Review - Thapa, Deepak (Far Western Journal of Education, 2025)
The integration of Confucian progressive educational principles into the Nepali educational landscape in general, and higher education system in particular, is a topic of growing interest lately. This thematic review critically explores the necessity and t effectiveness of integrating Confucian educational values to harmonize the Nepali education system. I utilized Systematic Literature Review (SLR) as a research method for collecting relevant papers available on the Google Scholar for the study. Scholarly i papers (n=11) on Confucian philosophy and education were systematically selected, using the certain key words like “Confucianism”, “Confucius education principles” & “Nepali education system”. I reviewed and synthesized n=11 articles against the research questions. The study focused on how Confucianism can be effectively integrated in Nepali education system and what could be the potential benefits of adopting this philosophy in Nepali higher education system. The findings of the study revealed that incorporation of Confucian progressive value-based educational principles along with Western centric academic knowledge would harmonize Nepali educational landscape. The dynamic interplay between moral education and academic knowledge would enable for holistic development of the individuals. Additionally, adaptation of Confucian curriculum, pedagogy and cross-cultural understanding would be crucial strategies for harmonizing Confucianism in Nepali higher education system. This study is significant because it encourages the educators, curriculum designers and policy makers to consider in adopting Confucian progressive value-based philosophy in Nepali education system which would ultimately enhance ethical values and promote social responsibility among Nepali Students.